Patient-specific PEEK implants for immediate restoration of temporal fossa after maxillary reconstruction with temporalis muscle flap - Sherif Ali; Omniya Abdel Aziz; Mamdouh Ahmed (SpringerOpen, 2022)
Abstract Background Temporal hollowing is a common complication following the rotation of the temporalis muscle that leaves the patient with a cosmetic impairment. Several alloplastic materials have been used to reconstruct the donor site; however, these implants need meticulous adaptation to conform the periphery of the defect and restore the contour of the temporal area. The aim of this study was to assess the use of patient-specific polyetheretherketone (PEEK) temporal implants to prevent temporal hollowing following the use of full temporalis muscle flap for large maxillary defects reconstruction. Methods This was a prospective study conducted on eight patients with major maxillary defects indicating the need of reconstruction with full temporalis muscle flap or any lesion indicating major maxillary resection and immediate reconstruction with total temporalis muscle flap. For each patient, a patient-specific PEEK implant was fabricated using virtual planning and milled from PEEK blocks. In the surgical theater, the temporalis muscle was exposed, elevated, and transferred to the maxilla. After the temporalis muscle transfer, PEEK implants were fixed in place to prevent temporal hollowing. Results The surgical procedures were uneventful for all patients. The esthetic result was satisfactory with no post-operative complications except in one patient where seroma occurred after 2 weeks and resolved after serial aspiration. Conclusion Patient-specific PEEK implant appears to facilitate the surgical procedures eliminate several meticulous steps that are mainly based on the surgeon's experience. Trial registration Clinical trials registration: NCT05240963 .